A meta-analysis of the capitalisation of CAP direct payments into land prices. (26th February 2021) - Varacca, Alessandro; Guastella, Giovanni; Pareglio, Stefano; Sckokai, Paolo
Abstract: The impact of the European Union common agricultural policy direct payments on land prices has received substantial attention in recent years, leading to heterogeneous evidence of capitalisation for both coupled and decoupled payments. In this paper, we provide an extensive review of the empirical works addressing this issue econometrically and compare their results through a Bayesian meta-regression model, focussing on the impact of decoupling and its implementation schemes. We find that the introduction of decoupled payments increased the capitalisation rate, although the extent of this increment hinges on the implementation scheme adopted by the member state.